Effects of grass silage-based feeding strategies and carcass weight on performance and environmental impacts of finishing beef on dairy crossbred heifers - Manni, Katariina; Hietala, Sanna; Pesonen, Maiju; Huuskonen, Arto (Elsevier, 2025)
When targeting low-carbon feed production and feeding cattle with non-human-edible feeds, in practice, this means maximising the use of forages such as grass. However, there is a gap in knowledge of the environmental impacts when carcass weight increases and/or concentrate is excluded from grass silage (GS)-based diet. The objective of this study was to evaluate the effects of two different GS−based diets and three carcass weights on performance and environmental impacts of growing heifers. The experiment was conducted using 84 crossbred heifers (Holstein or Nordic Red × Blonde d’Aquitaine). Two experimental diets were GS alone (GSA) and GS supplemented with barley grain (285 g/kg DM; GSB). Both diets contained a mineral-vitamin mixture (15 g/kg DM). The heifers were fed total mixed rations ad libitum. The animals were slaughtered at three BWs, targeting carcass weights of 300 (LCW), 325 (MCW) or 350 (HCW) kg. Life cycle assessment approach was used to compare climate change, eutrophication, and acidification impacts for both feeding treatments across three carcass weights. The experimental treatments had no effects on daily DM intake, but total DM intake was 13% higher for the GSA compared to GSB (P < 0.001) and 37% higher for HCW compared to LCW (P < 0.001). Barley grain supplementation increased daily energy intake by 14% (P < 0.001). Excluding barley grain from the diet decreased carcass gain by 20% (P < 0.001). Feed conversion (kg DM/kg carcass gain) declined when barley grain was excluded from the diet (P < 0.001). Carcass weight had no effect on growth rate and feed conversion. For GSA, the dressing proportion was 3% (P < 0.001) and carcass conformation 11% (P = 0.018) lower compared to GSB, but they were not affected by carcass weight. For carcass fat score, feeding × carcass weight quadratic interaction was observed (P < 0.016). Compared to GSA, GSB animals were fatter and carcass fat cover was affected to a greater extent by carcass weight. At the same carcass weight, the climate change impact of GSB was 10–11%, eutrophication potential 13–15%, and acidification potential 20–23% lower compared to GSA. Increasing carcass weight raised all impacts by 4–9% per functional unit within both dietary treatments. For all carcass weights, GSB showed consistently lower environmental impacts than GSA. In conclusion, including concentrate in the diet improved performance of the heifers and decreased environmental impacts.
Keywords: naudanlihantuotanto; ilmastovaikutus; väkirehu; elinkaariarviointi; kestävyys; beef production; climate change impact; concentrate; life cycle assessment; sustainability